Cardamine tangutorum O.E.Schulz (Brassicaceae), a new synonym of Cardamine macrophylla Willd - Jia-lu Li; Yi He; Quan-ru Liu (PhytoKeys)
Cardamine macrophylla Willd. and Cardamine tangutorum O.E.Schulz are both widely distributed plants of the genus Cardamine L. in East Asia, and they are regarded as the same species in Flora of China. In this study, through literature and specimen research, morphological measurement and phylogenetic analyses, the results show that the traditional distinguishing characters cannot distinguish the two species. Cardamine tangutorum O.E.Schulz inserted into the branch of Cardamine macrophylla Willd. in the molecular phylogenetic tree. Therefore, based on the results of this study, Cardamine tangutorum O.E.Schulz was treated as the synonym of Cardamine macrophylla Willd.